2022
DOI: 10.52547/jrdms.7.3.162
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Study of Patients with Chronic Vesiculobullous Lesions

Abstract: Background and Aim: Vesiculobullous diseases (VBDs) are characterized by the formation of vesicles or bullae. The aim of this study was to perform an epidemiological survey on patients with chronic VBDs referred to Shiraz Dental School during 2006-2016. Materials and Methods: In this retrospective cross-sectional study, epidemiological data (age, sex, prevalence, involvement location, prescribed medication, and underlying diseases) of patients diagnosed with VBDs were collected. The relationship between the ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Even though vesiculobullous disorders are generally more prevalent among females ( Maharshak and Brenner, 2002 , Rosi-Schumacher et al, 2023 ), the gender difference observed in patients with lichen planus was noticeable, with a male-to-female ratio of 1:6.25. Pemphigus vulgaris was the primary disorder in nearly half of the cases; however, the incidence and prevalence of lichen planus are much more than that of pemphigus vulgaris ( Lavaee et al, 2022 ). This may suggest that eye injury is relatively more related to pemphigus vulgaris.…”
Section: Discussionmentioning
confidence: 99%
“…Even though vesiculobullous disorders are generally more prevalent among females ( Maharshak and Brenner, 2002 , Rosi-Schumacher et al, 2023 ), the gender difference observed in patients with lichen planus was noticeable, with a male-to-female ratio of 1:6.25. Pemphigus vulgaris was the primary disorder in nearly half of the cases; however, the incidence and prevalence of lichen planus are much more than that of pemphigus vulgaris ( Lavaee et al, 2022 ). This may suggest that eye injury is relatively more related to pemphigus vulgaris.…”
Section: Discussionmentioning
confidence: 99%